Gamification in Information Technology Education: Its Impact on Motivation and Learning Outcomes: A Systematic Literature Review - Andi Nurqamal Ady Putra; Andi Gagah Purnama; Ayu Widya Listari; Herianti Herianti; Andi Hasri Tri Ulandari (Universitas Cahaya Prima, 2026)
Gamification has increasingly been implemented in technology-based learning environments to enhance students’ motivation and engagement. In the context of Information Technology Education (ITE), this approach is considered particularly relevant because learning materials are often abstract and require complex problem-solving skills. Although numerous studies report improvements in motivation through gamification, findings regarding its impact on cognitive learning outcomes remain varied and have not yet been comprehensively synthesized, particularly within the context of ITE. This study aims to systematically analyze how gamification influences motivation and learning outcomes, as well as to identify factors that determine its effectiveness. The method employed is a systematic literature review of national and international articles published between 2015 and 2026, sourced from indexed databases using structured selection criteria. The findings indicate that gamification consistently improves students’ learning motivation and engagement in Information Technology Education. However, its impact on cognitive learning outcomes varies depending on the quality of instructional design and the alignment between game elements and learning objectives.